2014
DOI: 10.1177/1461444814533067
|View full text |Cite
|
Sign up to set email alerts
|

Factors underlying male and female use of violent video games

Abstract: Research has consistently shown that males play violent video games more frequently than females, but factors underlying this gender gap have not been examined to date. The present approach examines the assumption that males play violent video games more, because they anticipate more enjoyment and less guilt from engaging in virtual violence than females. This may be because males are less empathetic, tend to morally justify physical violence more, and have a greater need for sensation and aggression in video … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 69 publications
4
28
0
1
Order By: Relevance
“…The reinforcing spirals model that examines individual differences in media selection side by side with media influence "draws from social identity theory (Tajfel and Turner, 1986), suggesting that media use in contemporary society is a principal means by which such social and personal identities are maintained" (Slater 2015, p. 371). Prior research had found that games that frequently feature violence tend to be played and enjoyed more by male than by female players (Hartmann et al 2015;Lucas and Sherry 2004;Rehbein et al 2016), thereby suggesting gender is a salient social identity variable in the phenomenon we have studied. Further, in the closest parallel to the current study in the existing literature, Gabbiadini and colleagues (2016) found that playing a violent and sexist game in the lab led to endorsement of "traditional" masculine norms only among males who showed identification with the main character.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The reinforcing spirals model that examines individual differences in media selection side by side with media influence "draws from social identity theory (Tajfel and Turner, 1986), suggesting that media use in contemporary society is a principal means by which such social and personal identities are maintained" (Slater 2015, p. 371). Prior research had found that games that frequently feature violence tend to be played and enjoyed more by male than by female players (Hartmann et al 2015;Lucas and Sherry 2004;Rehbein et al 2016), thereby suggesting gender is a salient social identity variable in the phenomenon we have studied. Further, in the closest parallel to the current study in the existing literature, Gabbiadini and colleagues (2016) found that playing a violent and sexist game in the lab led to endorsement of "traditional" masculine norms only among males who showed identification with the main character.…”
Section: Discussionmentioning
confidence: 81%
“…There is also evidence that the popularity of particular game genres differs by gender. Games that frequently feature violence, for instance, tend to be enjoyed and played more by men and boys than by women and girls (Hartmann, Möller and Krause 2015;Rehbein et al 2016), likely due to differing attitudes toward competition (Lucas and Sherry 2004) as well as moral concerns (Hartmann et al 2015).…”
Section: Media As a Source Of Gender Ideology Constructionmentioning
confidence: 99%
“…Múltiples estudios señalan que en el proceso de conformación del grupo de amigos, la agresión física entre varones aparece como medio de establecimiento de jerarquías sociales (p.e., CAMPO DÍAZ et al, 2012;CARD et al, 2008;AR-CHER, 2004), mientras que las niñas, responden de manera prosocial ante los conflictos (HOPMEYER & ASHER, 1997;CHUNG & ASHER, 1996) debido a un mayor desarrollo de la empatía (HARTMANN et al, 2015). Sin embargo, se ha encontrado que las niñas usan formas de agresión encubierta, usando mecanismos de exclusión social (BENENSON, 2013) y aunque suelen lograr relaciones más profundas y vinculantes (RUBIN et al, 1998), también son más frágiles y menos duraderas (BENENSON & CHRISTAKOS, 2003), presentando más dificultades que los varones para resolver los conflictos, que experimentan de forma intensa en términos emocionales que las lleva a tardar más en reconciliarse (BENENSON et al, 2014).…”
Section: Fatores Psicossociais Associados Ao Conflito Infantil Na Escolaunclassified
“…Poels et al (2012) examined the influence of masculinity and femininity on female players' motivations, play preferences, and favorite role in online role-playing games. In addition, recent research on gender and games stressed the necessity of including psychosocial or psychological gender constructs such as gender roles or gender identity in order to explain gendered gaming behavior (Hartmann, Möller, & Krause, 2015;Jensen & De Castell, 2010;Kowert et al, 2015).…”
Section: Examining Gendered Use Of Digital Games and Other Media Contentmentioning
confidence: 97%
“…In line with this, females' tendency to collaboration and avoidance of direct conflicts is related to their maternal instinct to protect their children (Graner Ray, 2004). Moreover, a traditional understanding of their gender role, for example, being empathetic and focusing on the maintenance of relationships, might keep them away from competitive as well as violent video game content (see Hartmann et al, 2015).…”
Section: Examining Gendered Use Of Digital Games and Other Media Contentmentioning
confidence: 99%